1997
DOI: 10.1136/sti.73.1.23
|View full text |Cite
|
Sign up to set email alerts
|

What is normal vaginal flora?

Abstract: OBJECTIVE: To observe the composition of the vaginal flora of healthy women over time, and in relation to hormonal changes, sexual activity, and hygiene habits. DESIGN: A longitudinal surveillance of the vaginal flora over an eight week period. SUBJECTS: 26 female health care workers in local genitourinary medicine clinics. METHODS: The participants were anonymised. They filled in diary cards daily. Blind vaginal swabs were self-taken two-seven times weekly. A smear was air-dried for later Gram staining. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
2
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 10 publications
2
71
2
4
Order By: Relevance
“…It was not powered for statistical analysis and is the first study, to our knowledge, to investigate the daily candidal colonization patterns observed during the luteal phase of the menstrual cycle in three women. Despite finding no previous studies that recorded the daily quantitative counts of Candida spp., one study concluded that colonization levels may fluctuate from day to day and persist for several days before resolving spontaneously (Priestley et al, 1997). This study supports this finding.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It was not powered for statistical analysis and is the first study, to our knowledge, to investigate the daily candidal colonization patterns observed during the luteal phase of the menstrual cycle in three women. Despite finding no previous studies that recorded the daily quantitative counts of Candida spp., one study concluded that colonization levels may fluctuate from day to day and persist for several days before resolving spontaneously (Priestley et al, 1997). This study supports this finding.…”
Section: Discussionsupporting
confidence: 82%
“…Several studies claim that colonization generally rises in the second half of the menstrual cycle (Larsen and Galask, 1982;Odds et al, 1987;Priestley et al, 1997). The development and rise of colonization levels before menstruation were noted in these case studies.…”
Section: Discussionmentioning
confidence: 94%
“…302 Although colonization of the lower genital tract by fecal flora can occur commonly without adverse consequences, 303,304 infection of the amniotic fluid, the interior of the placenta, and/or the fetus is associated with serious complications. 301 Chorioamnionitis or amniotic fluid infection has been identified as an important cause of fetal death in several studies from developing countries.…”
Section: Utis and Reproductive Tract Infectionsmentioning
confidence: 99%
“…De etiologia não definida 2 , a VB é conceituada hoje como uma alteração da flora vaginal em que os lactobacilos, normalmente predominantes, são substituídos por uma flora complexa abundante, dominada por bactérias anaeróbias estritas e facultativas 6,7 , podendo também ser observados padrões intermediários de flora vaginal em que os microrganismos anaeróbios e lactobacilos coexistem 3 . O estudo de Priestley et al 8 levanta dúvidas sobre o que deveria ser considerado flora vaginal normal, já que torna-se difícil interpretar o achado de VB em mulheres assintomáticas ou o achado de flora normal em mulheres sintomáticas. Também Caillouette et al 9 questionam se estas mulheres sem sintomas deveriam ser sempre tratadas, pois observaram, em seu trabalho, que a presença da Gardnerella na secreção vaginal antecedeu o achado de VB.…”
Section: Introductionunclassified